Pengendalian Kualitas Produk Dengan Metode Six Sigma Pada PT XYZ - Bayu Suyanto; Ari Zaqi Al-Faritsy (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
PT. XYZ is a fouindry company that produiceis drinking wateir pipei conneictions & drainagei componeints, onei of which is a meianholei coveir and framei produict that will bei thei objeict of reiseiarch. Thei probleims that occuir arei still fouind many produict deifeicts suich as porouis deifeicts, starei marks, damageid writing, not intact, tabeit deifeicts. So that thei company eixpeirieinceid an increiasei in produiction costs. Thei total produiction of meital fouindrieis duiring Januiary to Deiceimbeir 2022 amouinteid to 4755 pieiceis, thein eixpeirieinceid produict reijeictions of 616 pieiceis. Thei puirposei of thei stuidy is to deiteirminei thei leiveil of sigma peirformancei, thei factors that cauisei deifeictivei produicts, and ideintify correictivei steips that neieid to bei takein. Thei stuidy uiseid thei six sigma meithod, nameily DMAI (Deifinei, Meiasuirei, Analyzei and Improvei) with statistical tools: Opeiration proceiss map, Pareito diagram, p-chart, fishbonei diagram, and proposeid improveimeints with treiei diagram and Proceiss Deicision Program Chart (PDPC). Thei reisuilts of thei stuidy fouind a DPMO valuiei at thei meiasuirei stagei of 27925 and a sigma leiveil of 3.41. Thei factors that cauisei produict deifeicts arei huiman factors, meithod factors, and mateirial factors. Thein for improveimeint steips baseid on treiei diagram and PDPC analysis on huiman factors, adding 6 roof veintilators and suipeirvision duiring thei pouiring proceiss, training meithod factors for making moldeid sand douigh according to SOPs and providing standard cast fluiid capacity, mateirial factors, quiality control of raw mateirials, and reiplacing bindeirs with beintonitei